Dietary pattern and risk factors associated with newly diagnosed colorectal cancer and predictive factors for quality of life among survivors - Rashid, Ainaa Almardhiyah Abd (2024)
Colorectal cancer (CRC) is the second most common diagnosed cancer in Malaysia while the third in worldwide and Asia. This study had 3 phases: food frequency questionnaire (FFQ) validation, baseline and follow-up. The FFQ was developed specifically related to CRC risk consisted of 142 food items. At baseline phase, 341 patients (107 cases and 234 controls) enrolled to complete anthropometric assessments and questionnaire to predict risk factors and dietary pattern associated with CRC. Follow up assessment on anthropometric measurements and quality of life (QOL) using EORTC QLQ C30 and CR29 were performed after 6 months post diagnosis. As a result, this FFQ had good reproducibility and validity. Aged >51 years old (Odds ratio (OR) 7.72; 95% CI = 1.10–54.4), blood presence in stool (OR 6.30; 95% CI = 1.89–20.99), unintended weight loss (OR 21.95; 95% CI = 6.04–79.76) and reduced fat mass (OR 0.92; 95% CI = 0.85–1.00) had higher risk of getting CRC. Meanwhile the Processed diet pattern (OR = 3.45; 95% CI = 1.25–9.52) was found to be associated with CRC risk. The follow up study showed older patients and chronic stage predicts low QOL. In conclusion, the newly developed FFQ was good to assess dietary intake related to CRC in Malaysia. Predictor of CRC consisted of aged >51 years old, blood presence in stool, unintended weight loss, reduced fat mass and adherence to the Processed diet pattern. Predictive of low GHS/QOL was related to older patients and those with chronic stage of CRC. The risk factors of CRC, dietary pattern related to CRC and predictive factors of low QOL found in this study should be given more emphasis by policy makers and healthcare practitioners for the prevention and management of CRC patients in the future.